ECHOCARDIOGRAPHIC EVALUATION OF THE ATRIA IN SMALL ANIMALS - Paraguassu de Sá Rodrigues, Renan; Vieira Freitag, Flávio Augusto; Pinheiro dos Santos, Altair Aparecido; Gonçalves Sousa, Marlos (Archives of Veterinary Science, 2019)
Cardiac evaluation is often restricted to analysis of the ventricular chambers, and in particularthe left ventricle. The importance of atrial evaluation has previously been overlooked, but their importance as a representative of global cardiac function is now increasingly recognized. Evaluation of the atria allows more accurate diagnosis and monitoring of manyheart diseases. Echocardiography is a rapid, accessible, minimally invasive examination that can provide data onatrial morphology and function. The aim of this work was to analyze the main echocardiographic techniques with potential to be used in the evaluation of the atria in small animals.